2006
DOI: 10.1002/pmic.200500547
|View full text |Cite
|
Sign up to set email alerts
|

Proteins unique to intraphagosomally grownMycobacterium tuberculosis

Abstract: Pathogenic mycobacteria persist and replicate within phagosomes of host phagocytes by inhibiting phagosome maturation at an early endosome stage. The molecular basis for this behavior is not understood. To identify proteins of Mycobacterium tuberculosis unique to the intraphagosomal phase, mycobacteria were purified from phagosomes of infected murine bone marrow-derived macrophages and analyzed by high-resolution 2-DE and MS. Protein patterns of intraphagosomally grown M. tuberculosis were compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 70 publications
2
56
0
Order By: Relevance
“…Propionyl-CoA, as a precursor in several lipid biosynthetic pathways, including those for the (50). The oxidation of propionyl-CoA via the methylcitrate cycle would lead to toxic levels of 2-methylcitrate, which may account, at least in part, for the attenuated phenotypes of ICL and PrpD mutants in vivo (34,36,50), even if vitamin B 12 were available. ␤-Oxidation of odd-chain fatty acids comprising five carbons or more yields an acetyl-CoA subunit(s) in addition to propionyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propionyl-CoA, as a precursor in several lipid biosynthetic pathways, including those for the (50). The oxidation of propionyl-CoA via the methylcitrate cycle would lead to toxic levels of 2-methylcitrate, which may account, at least in part, for the attenuated phenotypes of ICL and PrpD mutants in vivo (34,36,50), even if vitamin B 12 were available. ␤-Oxidation of odd-chain fatty acids comprising five carbons or more yields an acetyl-CoA subunit(s) in addition to propionyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the possibility that the methylcitrate cycle might constitute the dominant pathway for propionate metabolism in vivo was investigated (37). The two key findings that motivated this investigation were the observed upregulation of methylcitrate cycle genes in the intracellular environment and in the mouse lung (34,48) and the inability of a ⌬icl1 ⌬icl2 double mutant of M. tuberculosis Erdman to grow on propionate in vitro or establish an infection in mice (36). The unusual involvement of icl1 and icl2 in both the methylcitrate cycle (as 2-methylisocitrate lyase [MCL]) and the glyoxylate cycle (as isocitrate lyase [ICL]) (18,37) in M. tuberculosis, however, complicates any interpretation of the relative importance of these pathways to M. tuberculosis metabolism.…”
mentioning
confidence: 99%
“…Interestingly, this cluster of genes is also upregulated in the phagosomes of infected murine macrophages, and Rv1129c and Rv1131 are active in infected mice . The function of Rv1130 is unknown, but the protein has been detected in phagosomes and may contribute to intracellular survival (Mattow et al, 2006). Rv1131 (gltA1) is predicted to encode citrate synthase, an enzyme of the TCA (Krebs) cycle (Cole et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have demonstrated that specific proteins can be upregulated in specific in vivo growth conditions, for example, within phagosomes (45). However, we know little about gene expression levels in M. tuberculosis as it is found in pulmonary cavities, inside granulomas, or even circulating in the blood of individuals with TB (46).…”
Section: Figurementioning
confidence: 99%